2011
DOI: 10.1007/s00442-011-2094-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of floral restrictiveness and stigma size on heterospecific pollen receipt in a prairie community

Abstract: Plant species vary greatly in the degree to which floral morphology restricts access to the flower interior. Restrictiveness of flower corollas may influence heterospecific pollen receipt, but the impact of floral morphology on heterospecific pollen transfer has received little attention. We characterized patterns of pollinator visitation and quantities of conspecific and heterospecific pollen receipt for 29 species with a range of floral morphologies in a prairie community dominated by the introduced plant Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 41 publications
(44 reference statements)
2
78
0
Order By: Relevance
“…E. vulgare and S. albicaulis) through chemical inhibitions (Wilcock and Neiland 2002). Our study showed that the presence of HP cannot be predicted from the presence of exotic plants alone, as has been reported previously (Montgomery and Rathcke 2012) and this suggests that pollen transfer may depend on flower morphology, with zygomorphic flowers (e.g. S. albicaulis) receiving less pollen than actinomorphic flowers (e.g.…”
Section: Traitsmentioning
confidence: 36%
See 3 more Smart Citations
“…E. vulgare and S. albicaulis) through chemical inhibitions (Wilcock and Neiland 2002). Our study showed that the presence of HP cannot be predicted from the presence of exotic plants alone, as has been reported previously (Montgomery and Rathcke 2012) and this suggests that pollen transfer may depend on flower morphology, with zygomorphic flowers (e.g. S. albicaulis) receiving less pollen than actinomorphic flowers (e.g.…”
Section: Traitsmentioning
confidence: 36%
“…On the one hand, the spatial distribution (Yang et al 2011), abundance (Lopezaraiza-Mikel et al 2007 and diversity (Ghazoul 2006) of plants are important factors for determining the constancy of pollinators to flowers; these factors could define the amounts of HP received by a focal species. On the other hand, flower morphology facilitates pollinator recognition and favours pollinator constancy in flowers, which reduces HP transfer (Schaefer et al 2004); additionally, flower morphology could act as a "barrier" to HP (Montgomery and Rathcke 2012;Ashman and ArceoGómez 2013). Specifically, HP deposit is less in bilateral flowers than in radial flowers (Montgomery and Rathcke 2012) because more open flowers are more susceptible to receiving pollen from different sources.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Ashman and Arceo-Gomez 2013;Fang and Huang 2013;Arceo-Gomez et al 2016a), though these studies highlight the great variation in HP deposition within individuals (range 0-95%) and species (range 0-80%), often linked to corolla and stigma morphology/size (e.g. Montgomery and Rathcke 2012). Effects of HP deposition on stigma interactions and the resultant success rates of conspecific pollen germination are highly varied between plants with obvious potential fitness costs for the plant (see Morales and Traveset 2008), and there may be particularly detrimental donors and particularly vulnerable recipients (Ashman and Arceo-Gomez 2013).…”
Section: Discussionmentioning
confidence: 99%